Latent tuberculosis among professionals from a referral hospital in oncology - Bavaresco, Ana Cristina Weber; Busatto, Caroline; Reis, Ana Julia; Krug, Suzane Frantz; Segatto, Nilza; De Moura Valim, Andréia Rosane; Nunes, Luciana de Souza; Stahlecker, Eloete; Hermes, Vanda; Nascimento, Thiago Prado; Carneiro, Marcelo; Possuelo, Lia Gonçalves (Clinical and Biomedical Research, 2017)
Introduction: Tuberculosis (TB) is an ancient contagious disease, and continues to be the leading cause of morbidity and mortality among infectious contagious diseases. It can be considered an occupational infectious disease when it happens in health professionals. These professionals are directly exposed to TB and are considered to be a high risk population for latent tuberculosis infection (LTBI) and active TB. The primary aim of this study was to estimate the prevalence of LTBI among the clinical and administrative staff of an oncology referral hospital in Rio Grande do Sul. The secondary aim of this study was evaluate tuberculin skin test (TST) conversion rate and the risk factors for TST positivity in this population. Methods: A cross-sectional study was carried out in a retrospective cohort with data collected in March 2013 and March 2014. Data of professionals from different hospital units were included. Those with induration ≥ 10 mm were considered as reactors, and conversion rate was assessed by an increase ≥ 10 mm in induration in the second TST compared with the first one. Results: Among the 225 professionals evaluated in 2013, 135 (60%) were reactors and 90 (40%) were non-reactors. The mean age was 32.9 (± 9.55), 176 (78.22%) were female, and most of the reactors worked in the hospital for 4 years or less. Non-reactors in 2013 were recommended to repeat the test in 2014, and the conversion rate was 9.37%. There was no significant difference in prevalence among the different professional categories, and the assessed risk factors were not associated with ILTB. Conclusions: The prevalence of LTBI in the study population was high, reinforcing the need to implement effective control measures to prevent LTBI in the hospital where the study was conducted. Keywords: Latent tuberculosis; occupational risk; tuberculin test; vulnerable populations